Association between the Stress Hyperglycemia Ratio Index and Short-term All-cause Mortality as well as ICU All-cause Mortality in Heart Failure Patients Receiving Invasive Ventilation: A Retrospective Study Based on the MIMIC-IV Database - Zhu, Pengcheng; Hu, Yuan (Journal of Cardiology and Cardiovascular Medicine, 2025)
Background: The stress-induced hyperglycemic ratio (SHR) is an index that reflects the imbalance between acute stress-induced glucose fluctuations and baseline glucose metabolism levels. Currently, there are few studies on the SHR index and its prognostic significance in heart failure (HF) patients undergoing invasive mechanical ventilation. This study aimed to investigate the relationship of SHR with the risk of death in HF patients requiring invasive ventilation. Methods: Conduct a retrospective cohort study based on the Medical Information Mart for Intensive Care IV (MIMIC-IV) database. Include adult heart failure patients who received invasive ventilation and divide them into quartile groups according to the level of the Systemic Heart Rate (SHR). The primary endpoints of the observation are the 30-day all-cause mortality rate and the all-cause mortality rate in the Intensive Care Unit (ICU), while the secondary endpoints are the 365-day all-cause mortality rate and the all-cause mortality rate during hospitalization. The Kaplan-Meier curve is used to compare the survival outcomes between groups. A Cox proportional hazards regression model that adjusts for demographic characteristics, underlying diseases, and the severity of critical illnesses is employed to evaluate the relationship between SHR and the mortality rate. The Restricted Cubic Spline (RCS) is utilized to test the nonlinear association between the two, and subgroup analysis is carried out to verify the consistency of the results across different groups. Results: Among the 1,038 eligible patients, the mean age was 68.50 years (range: 59.46 - 77.48 years), and 639 (61.56%) of them were male. The Kaplan-Meier curve showed that the higher the SHR index, the higher the risk of all-cause mortality in patients at 30 days (log-rank test, p = 0.011) and in the ICU (log-rank test, p = 0.0029). An increase in SHR was independently associated with an increased risk of 30-day and ICU mortality. Compared with the second quartile group Q2, the 30-day mortality rate in the group with the highest SHR was significantly higher (HR = 1.59, 95% CI 1.08, 2.33), and the ICU mortality rate in the group with the highest SHR was significantly higher (HR = 1.86, 95% CI 1.10, 3.14). The restricted cubic spline analysis showed a non-linear dose-response relationship between SHR and 30-day all-cause mortality (p for non-linearity < 0.05), and the risk of 30-day and ICU all-cause mortality gradually increased with the increase of the SHR index. The risks of 30-day and all-cause mortality in the ICU gradually increased. The results of the subgroup analysis confirmed that it remained stable in the subgroup of patients with Coronary Heart Disease (CHD). Conclusion: In critically ill heart failure (HF) patients receiving invasive ventilation, a higher stress hyperglycemia ratio (SHR) index is significantly associated with an increased risk of 30-day and all-cause mortality in the intensive care unit (ICU). Meanwhile, the SHR index is an independent predictor of mortality in critically ill HF patients who require invasive ventilation.